Measuring Entrepreneurial Skills and Sustainability in Small Business Enterprises Post-Pandemic: Empirical Study From Cross River State, Nigeria - Ukabi, Obeten B.; Uba, Uba J.; Ewum, Comfort O; Olubiyi, Timilehin O. (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
In an attempt to understand the underlying factors contributing to the high failure rate of small and medium-sized businesses in Nigeria, there is a need to focus on the extent to which the entrepreneurial skills of the operators impact the businesses. Therefore, the study aims to identify entrepreneurial skills required for sustainable small business enterprises in Calabar Metropolis of Cross River State, Nigeria. Two research questions were posed to guide the study. The study adopted a descriptive survey research design, and multistage sampling techniques was observed. The stratified and accidental sampling techniques were used to arrive at the selected sample of four hundred (400) registered small business enterprises operating in Cross Rivers State. A structured questionnaire titled “Questionnaire for Entrepreneurial Skills Required for Sustainable Small Business Enterprises in Calabar Metropolis” (QESRSSBECM) was used for data collection. The Cronbach Alpha Reliability test was used to determine the reliability of the instrument, which availed a high internal consistency of the instrument at 0.76 - 0.83. Descriptive statistics was used to analyze data gathered for the research using SPSS version 21.0. The research findings revealed that risk management and ICT skills are required for sustainable small business enterprises in Calabar Metropolis in the post-covid era. It was recommended, among others, that small business enterprise operators in Calabar Metropolis and Nigeria should be trained on developing their risk management practices and ICT capacities through advocacy, on-the-job training, seminars, and conferences.